STRUKTUR KEPEMILIKAN DAN KINERJA PERUSAHAAN KEUANGAN NON-CYCLICAL DI INDONESIA - Siti Nadya Ranjani Mulyani; Rina Ningtyas Wibowo; Farah Margaretha Leon (ITB AAS Indonesia Surakarta, 2025)
This study aims to analyze the effect of ownership structure on the financial performance of noncyclical companies in Indonesia. The ownership structure variables used include institutional ownership, foreign ownership, institutional ownership, ownership concentration, firm size, firm age, firm leverage, and firm liquidity. Firm performance is measured by Return on Assets as an internal factor. This study uses a quantitative approach with secondary data obtained from the annual reports of noncyclical companies listed on the Indonesia Stock Exchange (IDX) for the period 2020–2024. The sample was selected using purposive sampling based on the criteria of data availability and consistency. Data analysis was performed using panel data regression.